Syntheses, characterizations, crystal structures, DFT/TD‐DFT, luminescence behaviors and cytotoxic effect of bicompartmental Zn (II)‐dicyanamide Schiff base coordination polymers: An approach to apoptosis, autophagy and necrosis type classical cell death. (13th November 2019) - Majumdar, Dhrubajyoti; Agrawal, Yashika; Thomas, Renjith; Ullah, Zakir; Santra, Manas K.; Das, Sourav; Pal, Tapan K.; Bankura, Kalipada; Mishra, Dipankar
Abstract : Two new Zn (II)‐dicyanamide (dca) 1‐D chain coordination polymers (CPs), [Zn (L OMe )(μ1 ‐dca)(μ1, 5 ‐dca)]n (1) and [Zn (L OEt )(μ1 ‐dca)(μ1, 5 ‐dca)]n (2) have been successfully synthesized from bicompartmental Schiff base ligands N, N ′ ‐Bis(3‐methoxysalicylidenimino)‐1, 3‐diaminopropane (H2 L OMe ), N, N ′ ‐Bis(3‐ethoxysalicylidenimino)‐1, 3‐diaminoproane (H2 L OEt ) respectively and structurally characterized using various spectroscopic protocols like 1 H NMR, IR, Raman, UV–Vis, fluorescence as well as elemental analysis, TGA, PXRD and SCXRD studies. X‐ray single crystal study revealed that both the complexes have two different geometrical arrangement of Zn metal centres with distorted square pyramidal Zn(2) and trigonal prismatic geometry Zn(1). Ab‐initio DFT (Density functional theory) has been executed at B3LYP (Becke, 3‐parameter, Lee‐Yang‐Parr) using DGDVP (Diffuse gradient double valence polarised) basis set to explain FMO (Frontier molecular orbital), TD‐DFT (Time‐dependent density functional theory) and photovoltaic efficiency in Dye Sensitized Solar Cell (DSSC). Hirshfeld surface (HS) and 2D fingerprint plot analyses are shed more light on the non‐covalent supramolecular interactions. The steady state and time‐resolved fluorescence measurements have been conducted in DMSO and solid‐state. CPs exhibited bi‐exponential decay in DMSO as well as solid‐state where fluorescence behaviors are mainly intra‐ligand (π → π * ) in nature with lifetimes in the range (1.11–1.06 ns). In particular, in vitro cytotoxic activities were evaluated towards MCF7 (breast cancer) cell line, MDA‐MB‐231 (breast carcinoma) cell line and MCF10A (breast epithelial) cell line using MTT assay. CP1 had lower cytotoxic effect against MCF7 (20 μM), MDA‐MB‐231 (15 μM) cell lines in comparison with cisplatin (42.2 ± 8, 128.2 ± 7 μM). CP1 induced classical cell death apoptosis, autophagy and necrosis. Lower IC50 value of CP1 against MDA‐MB‐231 cell line provide new insights in the development of cancer therapeutics. Abstract : Two new Zn(II)‐dicyanamide 1‐D chain coordination polymers have been successfully synthesized from ortho vanillin derived Schiff base platforms and structurally characterized. Their photoluminescence and thermal properties, DFT/TD‐DFT, photovoltaic efficiency in Dye Sensitized Solar Cell (DSSC), cytotoxic effect, apoptosis, autophagy and necrosis type classical cell death were investigated in detail. Highlights: Two new Zn(II)‐dicyanamide CPs were synthesized and characterized X‐ray Crystal structures of Zn(II)‐CPs were determined DFT, TD‐DFT and luminescence behaviors have been explored Zn(II)‐CPs show noteworthy cytotoxic activity against breast cancer cell lines Apoptosis, autophagy and necrosis type classical cell death phenomenon was explained